2020
DOI: 10.1186/s13046-020-01689-6
|View full text |Cite
|
Sign up to set email alerts
|

A nicotine-induced positive feedback loop between HIF1A and YAP1 contributes to epithelial-to-mesenchymal transition in pancreatic ductal adenocarcinoma

Abstract: Background: Nicotine, an active ingredient in tobacco, can promote epithelial-to-mesenchymal transition (EMT) processes that enhance the aggressiveness of a number of human cancers. In the present study, we investigated whether cigarette smoke/nicotine drives EMT in pancreatic ductal adenocarcinoma (PDAC). Methods: Quantitative real-time PCR, western blot, immunohistochemistry, and immunofluorescence assays were used to evaluate Yes-associated protein 1 (YAP1) expression associated with cigarette smoking in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Interestingly, YAP1 has been shown to be involved in both oncogenic KRAS-dependent and KRAS-independent cancer-promoting activities ( 4 , 5 ). In recent years, YAP1 has been reported to participate in Epithelial-to-mesenchymal transition (EMT) process of tumor cells ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, YAP1 has been shown to be involved in both oncogenic KRAS-dependent and KRAS-independent cancer-promoting activities ( 4 , 5 ). In recent years, YAP1 has been reported to participate in Epithelial-to-mesenchymal transition (EMT) process of tumor cells ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…YAP is the coding product of the YAP1 gene, and Yang et al 40 found that YAP is a new regulator of NB cell proliferation, tumourigenesis and invasion, as well as an underlying target for treating cisplatin‐resistant NB. Previous studies have proved that YAP1 is widely involved in NB as an oncoprotein 16,17 . Meanwhile, tetrandrine (Tet) induces NB cell apoptosis by attenuating the Hippo/YAP1 pathway, 41 confirming that YAP1 is an oncogene in NB cells.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, inhibiting YAP1 hampers epithelial–mesenchymal transition (EMT) of pancreatic ductal adenocarcinoma 15 . Similarly, YAP1 is overexpressed in NB, and inhibiting YAP1 significantly represses NB cell proliferation, migration and invasion 16,17 . These reports indicate that YAP1 is implicated in NB, but whether SEV mediates NB progression through the miR‐144‐3p/YAP1 axis needs more exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking is a well-known risk factor for the occurrence and progression of malignant diseases [ 82 85 ]. Nicotine, the major constituent in cigarette smoke, plays key roles in cancer progression [ 86 89 ]. Nicotine likely promotes lung cancer cell proliferation by upregulating HIF-1 α and SOCC components [ 90 93 ].…”
Section: Discussionmentioning
confidence: 99%